Design aspects of used lubricating oil re-refining - Awaja, Firas (Elsevier, 2006)
Design Aspects of Used Lubricating Oil Re-Refining presents a feasible and comprehensive technology for recycling of used lubricating oils. This book discusses efficient and effective ways of reusing lubricating oil which, if implemented, will result in a better quality of life, the stability of the environment, the health of national economies and better relationships between nations. It presents essential experimental results for process designers and engineers to establish a complete process design. The conditions and behaviour in each step in the re-refining process, (dehydration, solvent extraction, solvent stripping, and vacuum distillation) are examined in order to discover ways to recover and reuse wastes that are produced by lubricating oils. Addresses and demonstrates the current knowledge of the process behaviour and re-refining technology of used lubricating oils Contains 94 figures and 22 tables that on results regarding the re-refining process behaviour of used lubricating oil Compares re-refined oil properties and their distillation behaviours to virgin and used oils.